2013
DOI: 10.1038/tpj.2013.40
|View full text |Cite
|
Sign up to set email alerts
|

HLA-A*31:01 and different types of carbamazepine-induced severe cutaneous adverse reactions: an international study and meta-analysis

Abstract: HLA-A*31:01 was reported to be associated with carbamazepine (CBZ)-induced severe cutaneous adverse reactions (SCAR), including drug reaction with eosinophilia and systemic symptoms (DRESS), Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). We conducted an international study using consensus diagnosis criteria to enroll a total of 93 patients with CBZ-SCAR from Europe or Asia. We found that HLA-A*31:01 showed a significant association with CBZ-DRESS in Europeans (P<0.001; odds ratio (OR) (95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
151
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(171 citation statements)
references
References 47 publications
12
151
1
4
Order By: Relevance
“…Th e liver is the most commonly involved organ in DRESS syndrome, and hepatitits, present also in our patient, occurs in about 80% of all cases (19,20,21). Th e degree of hepatitis is related to the interval between the onset of the syndrome and the discontinuation of the off ending drug.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Th e liver is the most commonly involved organ in DRESS syndrome, and hepatitits, present also in our patient, occurs in about 80% of all cases (19,20,21). Th e degree of hepatitis is related to the interval between the onset of the syndrome and the discontinuation of the off ending drug.…”
Section: Discussionsupporting
confidence: 52%
“…Aromatic anticonvulsants (phenytoin, phenobarbital, carbamazepine) and sulphonamides are the most common causative drugs, but a variety (18,(20)(21)(22)(23)(24)(25)(26)(27). Lamotrigine [6-(2,3-dichlorophenyl)-1,2,4-triazine-3,5-diamine] is an antiepileptic drug, used in the management of a broad range of seizures in adults and children which is not an aromatic antiepileptic, thus being structurally and pharmacologically unrelated to other antiepileptic medications e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical significance was defined as P < 0.05. (15). The authors found that HLA-A*31:01 had a sensitivity of 70% and a specificity of 96% as a predictor for CBZ-DRESS in Europeans, yet had a sensitivity of 50% and a specificity of 96% in Chinese.…”
Section: Discussionmentioning
confidence: 98%
“…[74][75][76][77][78] This association, however, was not consistently seen in subsequent studies many of which also reported a range of phenotypic variation among the carbamazepine induced IM-ADR observed. 77,[79][80][81] Work to more precisely define these associations and the structural basis for these interactions is ongoing.…”
Section: Drug-specific Models: Abacavirmentioning
confidence: 99%